(untitled) (International Journal of Language, Literacy and Translation, 2025)
This paper attempts to define the generic features of the hagiography of King Iyasu I, one of Gondärine’s acclaimed Kings, a?e Iyasu I (r. 1681-1706). It was written two years after the death of the king by aza? Sinoda in G???z. The literary genre of the hagiography of King Iyasu I is still a subject of scholarly debates. The contents and patterns of the hagiography are examined in comparison to the customary patterns of the previous hagiographical genre via entailing textual methods of analysis. Data were analyzed using content and thematic analysis. The article found that despite such linked and distinctive textual features, the hagiography of king Iyasu I appears to be one of the rare hagiographic texts in the history of the Ethiopic hagiography tradition. Apart from contributing our textual knowledge of hagiography, this paper confirms king Iyasu I is the only one among the monarchs of the Solomonic dynasty to have a hagiography composed to his name. It implies that Ethiopic hagiography had developed beyond the essentially edificatory goals of the Ethiopian Orthodox Church into a broader scope of contents and aims, particularly in the Gondärine period. This article is expected to be significant in examining the nature of Ethiopian hagiographic texts and their trends in keeping the narrative accounts about kings and their roles in historical periods.